2022
DOI: 10.3390/nano12040587
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Charging Times and Storage Properties of Nanoporous Supercapacitors

Abstract: An optimal combination of power and energy characteristics is beneficial for the further progress of supercapacitors-based technologies. We develop a nanoscale dynamic electrolyte model, which describes both static capacitance and the time-dependent charging process, including the initial square-root dependency and two subsequent exponential trends. The observed charging time corresponds to one of the relaxation times of the exponential regimes and significantly depends on the pore size. Additionally, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…C. Contributions of cations and anions to the total charge pore charge. Reproduced from ref . CC BY: Creative Commons Attribution.…”
Section: Dynamics Of Edl Chargingsupporting
confidence: 90%
See 3 more Smart Citations
“…C. Contributions of cations and anions to the total charge pore charge. Reproduced from ref . CC BY: Creative Commons Attribution.…”
Section: Dynamics Of Edl Chargingsupporting
confidence: 90%
“…Because of the crowding effects, counterion adsorption and co-ion release are strongly correlated. , While such correlation plays an important role for EDL charging in concentrated electrolytes, it is relatively insignificant for dilute solutions as described by the TL model. Based on the numerical results from the TDDFT calculations over a broad range of conditions, Aslyamov et al found that the two relaxation time scales can be estimated from where d and L are the pore width and length, respectively, ρ s ∞ is the total ion density inside the pore at equilibrium, ρ s ∞ (σ/2) is the total contact density, and φ s is the reduced surface potential. For charging a large pore at low electrolyte concentration, τ 1 becomes identical to τ TL .…”
Section: Dynamics Of Edl Chargingmentioning
confidence: 55%
See 2 more Smart Citations
“…Accordingly, Niya and Andrews studied the charging of porous conductive carbon materials [35] through the modified Poisson-Nernst-Planck (MPNP) equations [36]. Aslyamov, Sinkov, and Akhatov [37] used classical density functional theory to study slit pore charging. They unified all three known charging regimes: the pore's charge first increases as if it were semi-infinite (Q ∝ √ t), then slows down and approaches its equilibrium value exponentially with an RC time, and then slows down even further and equilibrates exponentially with the salt diffusion timescale [37].…”
Section: Introductionmentioning
confidence: 99%